Effects of acetylated distarch phosphate on the physicochemical characteristics and stability of the oyster sauce system - Li, Xiao; Zou, Feixue; Kang, Xuemin; Gao, Wei; Cui, Bo; Sui, Jie (Frontiers in Nutrition, 2024)
In this study, the effect of different acetylated distarch phosphate (ADSP) ratios (0, 1%, 2%, 3%, 4%, 5%) on the physicochemical characteristics and stability of the oyster sauce (OS) system was investigated. The texture, water state, interactions, rheological properties, microstructure, and stability of OS samples were analyzed through the texture analyser, low-field nuclear magnetic resonance (LF-NMR), particle diameter and zeta potential, fourier-transform infrared spectroscopy (FTIR), rheometer, and microscopes. The results revealed that the addition of ADSP improved the firmness, consistency, cohesiveness, and water-holding capacity of OS. Moreover, ADSP reduced the average particle size and zeta potential of OS, indicating that electrostatic and steric stabilization existed in the ADSP-OS system. The addition of ADSP enhanced the hydrogen bonding and decreased water mobility for OS system, processing a more continuous and smooth structure. All ADSP-OS samples were typical non-Newtonian fluids with shear-thinning characteristics. In addition, the non-significant instability index changes of ADSP-OS over the whole storage period confirmed the excellent long-term stabilization capability of OS prepared with ADSP. This study provides a theoretical basis for starch-based sauce products and contributes to the development of sauce products.